Analysis The Effect of Large-Scale Social Restrictions on Air Quality in DKI Jakarta - Prasetyo, Angga Dwi; Bashit, Nurhadi; Yusuf, Muhammad Adnan; Rassarandi, Farouki Dinda (Politeknik Negeri Batam, 2023)
The Covid-19 pandemic has caused all countries to implement strategies to suppress its spread, one of which is Indonesia, especially DKI Jakarta, which has implemented Large-Scale Social Restrictions (PSBB) since April 10 2020. Apart from being able to suppress the spread of the Covid-19 virus, PSBB is thought to have an impact on the environment, especially air quality in DKI Jakarta. According to research from the BMKG, Jakarta's air quality has improved over the last 5 years with the implementation of the PSBB. Besides analyzing the effect of the PSBB on air quality in DKI Jakarta, this research also aims to help governments in every region of Indonesia that do not have air quality monitoring stations. The method used in this study is to utilize Imagery from Sentinel-5P to measure concentrations of NO2, CO and SO2 gases validated using field data and utilize the NOAA Satellite acquired with Ventusky to analyze the effect of wind on the distribution of air pollution due to the PSBB. The results showed that the ratio of the average concentrations of NO2, CO and SO2 gases in DKI Jakarta decreased respectively to 27.70% ; 10.20% ; 42.06%. This shows an increase in air quality in DKI Jakarta due to the implementation of the PSBB. Comparison of the average concentrations of NO2, CO and SO2 gases in DKI Jakarta during the PSBB and after the PSBB increased slightly respectively to 11.92% ; 1.89% ; 35.84%. This shows that there is a decrease in air quality in DKI Jakarta which was caused after the implementation of the PSBB. Wind also affects the concentration of NO2, CO and SO2 gases. This is evidenced by the results of the correlation where the gas concentration is low when the wind speed is high, and vice versa. It was concluded that during the COVID-19 pandemic the concentrations of NO2, CO and SO2 in DKI Jakarta decreased and slightly increased after the PSBB, and wind could affect the distribution of these gases.